Analysis of the Higher Education Law of Argentina in relation to current trends - Calderón Arregui, David Alexander (2023)
The field of higher education is not static, since the frequent changes in society force countries to modify their regulations in an effort to assume the challenges presented in a resilient way, to remain at the forefront of education, since it is the how each society progresses globally. This article presents a comparative analysis of the Higher Education Law of Argentina (LES 24521) with the higher education legislation of Ecuador and Spain. The objective was to identify the weaknesses of LES 24521 compared to current trends in higher education legislation. It was developed within a qualitative methodology, and a descriptive exploratory design, since the policies and laws on relevant aspects in the management of higher education institutions (HEIs) were examined. Several weaknesses were found in the LES 24521, mainly in the aspects of university autonomy, budget, governance and administration, quality assurance, and teacher training. It is proposed that future reforms of the law address these deficiencies to guarantee quality higher education in Argentina, according to current challenges and the expectations of society.